Molecular detection of Theileria species, Anaplasma species, Candidatus Mycoplasma haemobos, Trypanosoma evansi and first evidence of Theileria sinensis-associated bovine anaemia in crossbred KedahKelantan x Brahman cattle - Ada Agina, Onyinyechukwu; Shaari, Mohd Rosly; Md Isa, Nur Mahiza; Ajat, Mokrish; Saad, Mohd Zamri; Mazlan, Mazlina; Muhamad, Azim Salahuddin; Kassim, Afrah Alhana; Lee, Chai Ha; Rusli, Fairuz Hazwani; Masaud, Darulmuqaamah; Hamzah, Hazilawati (BMC, 2021)
Background: Serious disease outbreaks in cattle are usually associated with blood pathogens. This study aims to detect blood pathogens namely Theileria species, Anaplasma species, Candidatus Mycoplasma haemobos and Trypanosoma evansi, and determine their phylogenetic relationships and haemato-biochemical abnormalities in naturally infected cattle. Methods: Molecular analysis was achieved by PCR amplification and sequencing of PCR amplicons of 18SrRN of Theileria species, 16SrRNA genes of Anaplasma and Mycoplasma species, MPSP genes of T. orientalis and T. sinensis, MSP4 gene of A. marginale, 16SrRNA gene of Candidatus Mycoplasma haemobos, and RoTat1.2 VSG gene of Trypanosoma evansi, in sixty-one (61) clinically ill Kedah Kelantan x Brahman cattle in Pahang, Malaysia. Results: A total of 44 (72.13%) cattle were infected with more than one blood pathogen. Theileria species was the blood pathogen with the highest molecular detection rate (72.13, 95% CI 59.83–81.81%). Nucleotide blast analyses of all sequences demonstrated high degree of molecular similarity (98–100%) in comparison with their respective reference sequences. Analysis of 18SrRNA gene sequences of Theileria species and 16SrRNA gene sequences of Anaplasma species revealed Theileria sinensis and Anaplasma platys respectively as additional species detected inthese cattle. MPSP-PCR analysis was conducted for further confirmation of T. sinensis. The blood picture of eight infected cattle groups revealed poikilocytosis, anisocytosis, rouleaux formation and degenerative left shift. High mean erythrocyte fragility values were common in infected cattle groups. Anaemia of the macrocytic normochromic type and spherocytes were observed in the T. evansi and Anaplasma platys + Theileria sinensis double species co-infected cattle group. Normocytic normochromic anaemia was observed in the T. sinensis infected cattle group. Significant (p < 0.05) increases in serum liver and kidney parameters, total protein, globulin, total and unconjugated bilirubin and decreased albumin values were observed in the T. evansi infected cattle when compared to clinically healthy cattle. Conclusion: We present the first evidence of Theileria sinensis-associated bovine anaemia (TSABA) in Malaysian cattle. Because of the high occurrence of bovine theileriosis and detection of A. platys, there is an urgent need for appropriate preventive and control measures against these blood pathogens.